The state of the world’s animal genetic resources for food and agriculture - Rischkowsky, Barbara (Commission on Genetic Resources for Food and Agriculture, Food and Agriculture Organization of the United Nations, 2007)
The State of the World's Animal Genetic Resources for Food and Agriculture" is the first global assessment of these resources. Drawing on 169 Country Reports, contributions from a number of international organizations and 12 specially commissioned thematic studies, it presents an analysis of the state of agricultural biodiversity in the livestock sector - origins and development, uses and values, distribution and exchange, risk status and threats - and of capacity to manage these resources - institutions, policies and legal frameworks, structured breeding activities and conservation programmes. Needs and challenges are assessed in the context of the forces driving change in livestock production systems. Tools and methods to enhance the use and development of animal genetic resources are explored in sections on the state of the art in characterization, genetic improvement, economic evaluation and conservation.